Delta and jagged are candidate target genes of RNAi biopesticides for the control of Nilaparvata lugens - Yang, Xifa; Liu, Shaokai; Lu, Wenhui; Du, Mengfang; Qiao, Zhuangzhuang; Liang, Zhen; An, Yiting; Gao, Jing; Li, Xiang (Frontiers in Bioengineering and Biotechnology, 2022)
The brown planthopper (BPH; Nilaparvata lugens) is an important pest in rice cultivation, and chemical pesticide over-use and ineffectiveness of existing Bt transgenic rice against piercing-sucking insects make novel control methods necessary. RNA interference (RNAi) biopesticide is a new type of product with high efficiency and specificity and are simple to use. The Notch signaling pathway has extensive and important physiological functions and plays a key role in the development of insects. In this study, two key ligand genes of the Notch signaling pathway, delta (dl) and jagged (jag), were selected and their lethal effects and functional analysis were systematically evaluated using a stable short-winged population (Brachypterous strain) and a long-winged population (Macropterous strain) of BPHs. The full-length coding sequences of Nldl and Nljag comprised 1,863 and 3,837 base pairs, encoding 620 and 1,278 amino acids, respectively. The nucleic acid sequences of Nldl and Nljag were identical between the two strains. The expression levels of Nldl and Nljag were relatively high in the head of the nymphs, followed by those in the abdomen. Through RNAi treatment, we found that injection of BPH nymphs of both strains with dsNldl (10-50 ng/nymph) or dsNljag (100 ng/nymph) produced lethal or teratogenic effects. dsRNA treatment showed excellent inhibitory effects on the expression of target genes on days 1 and 5, suggesting that RNAi rapidly exhibits effects which persist for long periods of time in BPHs. Taken together, our results confirm the potential of Nldl and Nljag as target genes of RNAi biopesticides, and we propose optimized dosages for the control of BPHs.